Correlation Of Social Support And Attitudes PUS Women With Early Detection Of Cervical Cancer IVA Method In The Public Health Center Of Martapura 2 Banjar Districts On 2019 - Rahayu, Dinah (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
One of the efforts to reduce cervical cancer patients is early detection of cervical cancer using IVA method and factors early detection servical cancer in IVA method are social support and attitudes of PUS women. Data from Martapura 2 Public Health Center Banjar Distric IVA examination on 2017 with 360 targets and there were 250 (69,41%) women who conducted IVA examinations, on 2018 with a target of 700 and only 242 (41,63%) women who examined IVA. To Determine the correlation social support and attitudes of women with early detection of cervical cancer IVA method in The Public Health Center Martapura 2 Banjar Districts on 2019. Analytical survey research method using cross sectional appoarch. The population was all women couple of reproductive age in The Public Health Center Of Martapura 2 Banjar Districts on 2019, amounting to 100 people of sample. Sampling uses purposive sampling. The instrument used a questionnarie. Analysis data used chi-square statistical test (α < 0,05). Examinations conducted IVA 50 respondents (50,0%), positive social support 51 respondents (51,0%), positive attitude used 74 respondents (74,0%). The statistical test result show the correlation social support for early detection of servical cancer method IVA (p = 0,000 < α 0,05) and correlation attitudes early detection of cervical cancer method IVA (p = 0,000 < α 0,05). There was a correlation social support and attitudes of women couple of reproductive age early detection of cervical cancer in the IVA method In The Public Health Center Of Martapura 2 Banjar Districts On 2019.